Variability of antioxidant properties, catechins, caffeine, L-theanine and other amino acids in different plant parts of Azorean Camellia sinensis - Paiva, Lisete S. (2022)
During Camellia sinensis tea processing, manufacturers usually remove the internodes, which are classified as waste. This study presents the first determination of plant part contribution, particularly internodes, to green tea quality, in order to find the best blend to maximize impact on human health. Catechins, caffeine and free amino acid (FAA) profiles were determined by RP-HPLC/DAD, total phenolics (TPC) and total flavonoids (TFC) by FolinCiocalteu and colorimetric methodologies, respectively, and antioxidant activities by free radical-scavenging activity (FRSA), ferric-reducing antioxidant power (FRAP) and ferrous ion-chelating (FIC) methods. Individual esterified catechins content decreased as follows: epicatechin-3-gallate > epigallocatechin-3-gallate ≫ gallocatecin-3-gallate, and epicatechin derivatives content ranged from 63.91 to 91.22% of total catechins. Caffeine content was higher in internodes. L-theanine, histidine, asparagine, phenylalanine, glutamic acid and methionine were the major FAAs, and internodes contained the highest amounts of L-theanine and histidine (17 and 13.73 mg/g of sample, respectively). TPC ranged from 201.51 to 265.48 mg gallic acid equivalents/g dry extract (DE) and TFC ranged from 23.84 to 72.02 mg rutin equivalents/g DE. Internodes presented the lowest FRSA (EC50 ¼ 6.10–13.50 μg/mL), FRAP (EC50 ¼ 5.70–11.40 μg/mL) and FIC activity (36.96–79.21%). Bud presented the highest FRSA and FRAP, and budþ1stþ2ndleaves þ internodes the highest FIC activity. The results revealed the potential contribution of the internodes to green tea quality and, consequently, to human health.